2017
DOI: 10.1002/dc.23713
|View full text |Cite
|
Sign up to set email alerts
|

Fine social aspiration: Twitter as a voice for cytopathology

Abstract: Social media is an influential tool that has the power to transform cytopathology. Twitter is being used more and more to share cutting-edge updates from pathology meetings ("live-tweeting"). Modern smartphones can now take high resolution microscopic photographs and easily transmit them worldwide via Twitter, Facebook, and other social media, allowing cytopathologists to share educational pearls and discuss difficult cases on a global scale like never before. Social media also allows cytopathologists to share… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 11 publications
0
14
0
1
Order By: Relevance
“…This pathologist has been involved in various Facebook support groups by interacting with patients and their families, explaining what pathologists do and pathology terminology, helping them navigate the cancer care system, answering general questions, and providing reliable information to educate these patients about their disease. 3,[5][6][7][8][9] Anecdotally, the patients reported that they enjoy having this pathologist in their groups and find the pathologist's posts and comments helpful. In this study, we aimed to more formally assess patients' perceptions of pathologist involvement in their Facebook support groups.…”
mentioning
confidence: 99%
“…This pathologist has been involved in various Facebook support groups by interacting with patients and their families, explaining what pathologists do and pathology terminology, helping them navigate the cancer care system, answering general questions, and providing reliable information to educate these patients about their disease. 3,[5][6][7][8][9] Anecdotally, the patients reported that they enjoy having this pathologist in their groups and find the pathologist's posts and comments helpful. In this study, we aimed to more formally assess patients' perceptions of pathologist involvement in their Facebook support groups.…”
mentioning
confidence: 99%
“…With any new and emerging technology, early adopters risk judgment. However, social media have already had significant uptake in the cytopathology community, including journals such as Cancer Cytopathology and Diagnostic Cytopathology , societies such as the American Society of Cytopathology (ASC) and the Papanicolaou Society of Cytopathology, the Milan reporting system, the current ASC president, the current editor‐in‐chief of Cancer Cytopathology , and many others . Do's and don'ts for sharing cytopathology on social media are highlighted in Table .…”
Section: Do's and Don'ts Of Posting On Social Mediamentioning
confidence: 99%
“…Live tweeting is an excellent way to be in 2 places at once, both for those at the meeting so that they can see what is being presented in concurrent sessions and for those unable to attend the meeting so that they can also benefit from the information shared. For example, Twitter activity from the United States and Canadian Academy of Pathology annual meeting increased from 1746 tweets at the 2015 meeting to 6524 tweets at the 2016 meeting, and the 2016 ASC annual meeting had approximately 4000 tweets . The real‐time nature of social media also allows discussion of novel findings or guidelines with both those at the meeting and those covering service back at home.…”
Section: Do's and Don'ts Of Posting On Social Mediamentioning
confidence: 99%
“…2 Facebook, Twitter, and other social media platforms provide numerous potential benefits to the global pathology community. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Despite this growing popularity and acceptance, some pathologists are still reticent to use social media professionally. 22,23 One of the authors (J.M.G.)…”
mentioning
confidence: 99%